Eudesmanes from Pluchea sagittalis. Their antifeedant activity on Spodoptera frugiperda - Vera, Nancy Roxana (2008)
Eudesmane-type sesquiterpenoids 3α-(2,3-epoxy-2-methylbutyryloxy)-4α-formoxy-11-hydroxy-6,7-dehydroeudesman-8-one (1) and 3α-(2,3-epoxy-2-methylbutyryloxy)-4α,7α,11-trihydroxyeudesman-8-one (2), together with 10 known structurally related eudesmanes were isolated from the CHCl3 extract of aerial parts of Pluchea sagittalis (Lamarck) Cabrera. Their structures were deduced by extensive application of 1 and 2D NMR spectroscopic techniques and high and low resolution CIMS. X-ray crystallographic analysis of the known compound 3α-(2,3-epoxy-2-methylbutyryloxy)-4α-formoxycuauthemone (9) is reported here for the first time, and confirms the structural features for the series of the reported eudesmanes. All eudesmanes were tested for their antifeedant activity by incorporating them to an artificial diet of larvae of the polyphagous insect Spodoptera frugiperda at a concentration of 100 ppm. Our results, from feeding choice tests, indicated that most of the compounds deter larval feeding at the cited concentration. © 2008 Elsevier Ltd. All rights reserved.